2022
DOI: 10.3390/ijerph19116827
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Patients with Marfan Syndrome—Polish Study

Abstract: Background: Despite extensive knowledge about the quality of life of people suffering from rare diseases, data on patients with Marfan syndrome (MFS) are scarce and inconsistent. Hence, the problem of assessing the quality of life (QOL) and its relationship with the assessment of which ailments are the most burdensome for these patients is still open. Aim: Comparison of the quality of life of patients with MFS and determination as to which of the reported complaints in patients with MFS are related to the QOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown the impact of MFS and its psychological impairment on Quality of Life (QoL) [ 33 36 , 39 41 ]. However, only one study investigated the OHRQoL in people with MFS in Germany, and the results suggested that people with MFS show a reduced OHRQoL (OHIP-G14: 13.65 ± 13.53 ) compared to the general population [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the impact of MFS and its psychological impairment on Quality of Life (QoL) [ 33 36 , 39 41 ]. However, only one study investigated the OHRQoL in people with MFS in Germany, and the results suggested that people with MFS show a reduced OHRQoL (OHIP-G14: 13.65 ± 13.53 ) compared to the general population [ 6 ].…”
Section: Discussionmentioning
confidence: 99%